Fish fauna from Río Pilcomayo National Park and Ramsar Site and its surroundings, Formosa, Argentina - Brancolini, Florencia (2014)
Fil: Brancolini, Florencia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Instituto de Limnología Dr. Raúl A. Ringuelet; Argentina